The American Community Survey : summary of a workshop (National Academy Press, 2001)
The American Community Survey (ACS), to be run by the Census Bureau, will be a large (250,000 housing units a month), predominantly mailout/mailback survey that will collect information similar to that on the decennial census long form. This title summarizes that workshop.